Potensi Mikroba Asal Tanah Hutan dan Limbah Organik sebagai Produsen Amilase, Lipase, dan Selulase untuk Aplikasi Industri - Telaumbanua, Jun Mardin; Bate’e, Riston Iman; Hulu, Adil Hati; Waruwu, Linda Fatmawati; Zega, Novelina Andriani (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Hydrolytic enzymes such as amylase, lipase, and cellulase play a strategic role in various modern industrial sectors. Microorganisms isolated from forest soil and organic waste exhibit high enzyme production capabilities due to their ecological adaptation to complex substrates. This literature review examines the potential of local Indonesian microbes as a source of industrial enzymes through a systematic analysis of national research conducted during the 2015–2024 period. This study applies data analysis techniques including data reduction, data presentation, and conclusion drawing to synthesize the findings. Indonesian tropical forest soils harbor a diversity of enzyme-producing microbes with varying specific activities. Organic waste such as bagasse and fruit peels provide habitats for microbes capable of producing extracellular enzymes. The results of the literature synthesis indicate that bacterial and fungal isolates from both sources have commercial prospects for applications in the food, textile, bioenergy, and bioremediation industries. Optimizing culture conditions and large-scale production strategies are key to the successful utilization of local microbes. This study provides recommendations for further research leading to the industrialization of Indonesian microbe-based enzymes.